2015
DOI: 10.1016/j.triboint.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between gear contact friction and ball on disc friction measurements

Abstract: Running experiments with full-size gearboxes from the actual application has the advantage of giving realistic results in terms of power losses. The drawback is extensive costs, lengthy testing, and the difficulty in differentiating between load dependent and load independent losses, and which losses are coming from the gears, seals, bearings or synchronizers. In this work, the correlation between friction measurements conducted in a ball-on-disc machine and friction measurements conducted in a back-to-back ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Mapping out the friction coefficient over a large range of entrainment velocity and slip provides an excellent measure of general lubricant and surface properties, and the information gained can be correlated to gear tooth mesh behavior. 22 However, to accurately simulate the running-in for a gear tooth, a somewhat different procedure must be used. Any point along the gear tooth face in a spur gear contact will experience a single value of slip with the entrainment velocity changing as the gear is started, operated at various speeds, then stopped.…”
Section: Constant Slipmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping out the friction coefficient over a large range of entrainment velocity and slip provides an excellent measure of general lubricant and surface properties, and the information gained can be correlated to gear tooth mesh behavior. 22 However, to accurately simulate the running-in for a gear tooth, a somewhat different procedure must be used. Any point along the gear tooth face in a spur gear contact will experience a single value of slip with the entrainment velocity changing as the gear is started, operated at various speeds, then stopped.…”
Section: Constant Slipmentioning
confidence: 99%
“…Björling et al have used friction mapping with entrainment velocity and slip to study friction coefficient, surface roughness, lubricant viscosity and type, surface material, and lubrication regime. [19][20][21][22] By mapping over these variables during the running-in process, we can also study the contact history that cause running-in and the friction coefficient that one can expect during and after the running-in process.…”
Section: Introductionmentioning
confidence: 99%
“…The disc's diameter was in 10.16 cm, and the balls were in diameter of 2.063 cm under different types of lubricant. The test was performed under 76 N load, speeds of 1 m/s to 4 m/s, with temperatures of 40 o and 70 o , pressure of 1.24 GPa, and 0.0002 -1.2 Slide to Roll Ration (SRR)[42]. EHL tribological systems is presented by Björling et al with different parameters and conditions.…”
mentioning
confidence: 99%
“…5 different engine oil formulations were used, however, it should be mentioned that the viscosity effect was only studied indirectly varying the temperature from 30°C to 140°C, the different formulations corresponded to different degrees of fricton modifier additives. The study found a significant engine friction reduction as temperature risen, the authors claimed correlations of those friction tests with previous fuel economy tests, concluding that a 11% friction reduction led to 1% fuel economy differences [60].…”
Section: Japan Legislationmentioning
confidence: 84%
“…In order to complete the engine and fleet tests, two tribometers were used to mimic certain ICE tribocontacts; the Cameron Plint Machine TE77 reciprocating rig, widely used to reproduce the piston ring/cylinder liner contact [47][48][49][50][51][52][53][54][55] and the WAM Ball-onDisc machine, which is normally used to reproduce valvetrain and transmission gears tribocontacts [56][57][58][59][60] were used alongside some of the engine oils used in the fleet test.…”
Section: Tribometers Laboratory Tests and Equipmentmentioning
confidence: 99%